Profit-Sharing Rules and the Taxation of Multinational Internet Platforms - Francis Bloch; Gabrielle Demange (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper analyzes taxation of an Internet platform attracting users from different jurisdictions. When corporate income tax rates are different in the two jurisdictions, the platform distorts prices and outputs in order to shift profit to the low-tax country. We analyze the comparative statics effects of an increase in the tax rate of one country. When cross-effects are present in both countries, the platform has an incentive to increase the number of users in the high-tax country and decrease the number of users in the low-tax country. When externalities only flow from one market to another, an increase in the corporate tax rate results either in a decrease or an increase in the number of users in both countries depending on the direction of externalities. We compare the baseline regime of separate accounting (SA) with a regime of formula apportionment (FA), where the tax bill is apportioned in proportion to the number of users in the two countries. Under FA, an increase in the corporate tax rate increases the number of users in the low-tax country and decreases the number of users in the high-tax country. We use a numerical simulation to show that the high-tax country prefers SA to FA whereas the low-tax country prefers FA to SA.
Keywords: H32; H25; L12; L14; 330; digital platforms; multinational firms; corporate income taxation; formula apportionment; separate accounting